2016
DOI: 10.1080/15599612.2016.1166304
|View full text |Cite
|
Sign up to set email alerts
|

Development of an optical inspection platform for surface defect detection in touch panel glass

Abstract: An optical inspection platform combining parallel image processing with high resolution opto-mechanical module was developed for defect inspection of touch panel glass. Dark field images were acquired using a 12288-pixel line CCD camera with 3.5 µm per pixel resolution and 12 kHz line rate. Key features of the glass surface were analyzed by parallel image processing on combined CPU and GPU platforms. Defect inspection of touch panel glass, which provided 386 megapixel image data per sample, was completed in ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…The present work improves on the AOI apparatus reported in Chang et al [6] in terms of simultaneous execution of defect detection and classification. The detection is based on the principle that the presence of defects on the specimen will scatter light toward the detection plane of a linear CCD camera.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…The present work improves on the AOI apparatus reported in Chang et al [6] in terms of simultaneous execution of defect detection and classification. The detection is based on the principle that the presence of defects on the specimen will scatter light toward the detection plane of a linear CCD camera.…”
Section: Introductionmentioning
confidence: 58%
“…In this study, the construction of AOI equipment is shown in Figure 1, where both the imaging module and specimen stage are controlled automatically by a software package custom developed for the AOI system for image processing and hardware controls. [6] The imaging module consists of 12,288 pixel-line CCD camera (Basler raL12288-66 km) with 3.5 µm per pixel resolution and lens assembly. The illumination is provided by an light emitting diode (LED) array positioned a few centimeters above the specimen stage.…”
Section: Optical Inspection Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 22(a) shows the difference in detecting the defects using conventional light source and striped light source. Chang et al in [288] offered an AOI system to filter and classify touch panel glass defects. Their illumination setting consisted of two LED lights with fan-shaped light transmission.…”
Section: A Contrast and Illumination Settingsmentioning
confidence: 99%
“…In addition, Ming Chang et al [ 11 ] presented the development of an optical inspection platform that combines parallel image processing with high resolution opto-mechanical module for the detection of defects of touch panel glass. This work proposes the implementation of a custom illumination source to improve the scattering efficiency of the surface, while improving the contrast of the obtained images and the performance of the vision inspection system.…”
Section: State Of the Artmentioning
confidence: 99%